2018
DOI: 10.4052/tigg.1764.1e
|View full text |Cite
|
Sign up to set email alerts
|

Glycan Remodeling of Glycoproteins Using ENGases

Abstract: Recently, homogenous glycoprotein has been prepared by using a chemoenzymatic approach to investigate the function of glycoproteins. Glycoproteins produced by cultured cells generally have heterogeneous glycans, so it is unclear which glycan is associated with the function of the glycoprotein. Moreover, because glycoproteins are heterogeneous, it is difficult to analyze their structure by X-ray crystal diffraction or NMR measurement. To solve this problem, transgenic cells have been developed to produce homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…It has been reported that many kinds of N-glycans can be prepared from the hen egg-derived glycan using chemical or enzymatic methods (12)(13)(14)(15)(16)(17). There are many reports on the synthesis of glycoproteins and glycopeptides using complex and high-mannose-type sugar chains obtained from natural products such as chicken eggs and soybeans (18)(19)(20).…”
Section: A Introductionmentioning
confidence: 99%
“…It has been reported that many kinds of N-glycans can be prepared from the hen egg-derived glycan using chemical or enzymatic methods (12)(13)(14)(15)(16)(17). There are many reports on the synthesis of glycoproteins and glycopeptides using complex and high-mannose-type sugar chains obtained from natural products such as chicken eggs and soybeans (18)(19)(20).…”
Section: A Introductionmentioning
confidence: 99%